1963
DOI: 10.1111/j.2044-8295.1963.tb00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Memory Span and the Skewness of the Serial‐position Curve*

Abstract: Three experiments were performed to test the hypothesis that the skewness of the serial‐position curve is determined, at least in part, by memory span. Expt. I showed that the degree of skewness of the serial‐position curve is positively related to the length of the subject's immediate memory span. Memory span for sequences of colour‐forms was determined for 47 subjects (university students). Eleven subjects with the highest span (HS) and 11 subjects with the lowest span (LS) were compared in the serial learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
3
0

Year Published

1964
1964
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…Waugh (1960) found that the improved performance of well-practiced subjects occurred in the primacy portion of the serial position curve and that the recency portion was unaltered. A similar result was obtained in comparing subjects with high and low memory spans (Jensen & Roden, 1963).…”
Section: Practice Effects In Regular Laboratory Studiessupporting
confidence: 83%
See 1 more Smart Citation
“…Waugh (1960) found that the improved performance of well-practiced subjects occurred in the primacy portion of the serial position curve and that the recency portion was unaltered. A similar result was obtained in comparing subjects with high and low memory spans (Jensen & Roden, 1963).…”
Section: Practice Effects In Regular Laboratory Studiessupporting
confidence: 83%
“…Greater reduction was observed for two subjects given 30-40 practice sessions. Similar dramatic improvements have been observed for lists of nonsense syllables (Ebert & Meumann, 1904; Lepley, 1934; Meyer & Miles, 1953; Ward, 1937), lists of coloured geometric forms (Jensen & Roden, 1963), and for learning of paired-associates (Greenberg & Underwood, 1950; Keppel, Postman, & Zavortnik, 1968; Warr, 1964, Exp. 1).…”
Section: Memory Skill Versus Memory Ability In Normal Subjectssupporting
confidence: 60%
“…Figures 3 and 4 are provided merely as comparative data to illustrate differences in mean errors for each level at each position under both tasks. These results would seem to confirm the astmmptions made concerning an increase in retention (or conversely fewer errors and 1;hus more efficiency) with age (Edwards & Scannell, 1968; Jensen & Roden, 1963). I t will be recalled that the raw error data were converted into Index scores on which the actual discriminant analysis was performed.…”
Section: Resultssupporting
confidence: 63%
“…Waugh (1960) presented a theory relating memory span to the serial position effect which involved a hypothesis concerning an interaction between Ss memory span and differential recall of sections of serial lists. Jensen & Roden (1963), in Experiment I, found no difference between high and low memory span groups on trials to criterion with the high span group making significantly fewer errors in the first four positions thereby indicating a difference in the skewness of the curves for the groups.…”
mentioning
confidence: 73%